The Profile of Undergraduate Students' Ability in Writing Exposition Text - Permatasari, Silvy; Fiki Susanto, Allvian Ika (Faculty of Language and Literature, University of Surakarta, 2024)
This study was aimed to identify the ability of first-semester students' class of 2023/2024 in writing analytical exposition texts according to CEFR level at UNK Semarang and identify the problems faced as well as solutions to these problems. The data were taken from 35 students' writing products and the results of interviews with several students. Data analysis for assessment writing will use Ratnaningsih' theory and CEFR. This research uses mixed methods, in the first stage the researchers will carry out a quantitative method first (calculating writing test scores) and then the researchers will carry out a qualitative method (interviews). The results of this study showed that the writing skill level of participants is at level C1, where the highest aspect obtained by most students is content and the lowest aspect is mechanics. Apart from that, the main problems in writing analytical exposition text are grammar, vocabulary, spelling, punctuation, and capitalization. Lastly, researchers can propose for the problems in this study is to increase or diligently practice writing in English, note down a new vocabulary that has never been known before and increase knowledge with various kinds of references found, for example from YouTube.